STRATEGI KOPING: UPAYA RESILIENSI IBU ANAK DISABILITAS DI SLB DHARMA ASIH PONTIANAK - Vify Anggraeni Solikhin; Pabali Musa; R. Nunung Nurwati; Agustus Fajar Senjaya; Victoria Novita Sari; Brigita Anjelia; Lusia Wini Linasari; Risky Aditya (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
Resilience is an individual's strength in solving problems when situations are complicated. This research can help mothers and children build and find the source of their resilience, which makes a mother and her disabled child not give up quickly to become a functioning human being in society. This research used descriptive qualitative research methods, in-depth interview techniques, and literature studies. The coping strategy used by Mrs A with her child, who is deaf, is one form of effort to increase her resilience. This shows the importance of support and self-adjustment in facing complex challenges associated with caring for children with special needs. This research can further explore how environmental and social factors can influence Mrs A's implementation of coping strategies. Focusing on resilience makes it easier for Mrs A to face challenges and problems associated with caring for her child.